High Prevalence of Metabolic Syndrome in First-Degree Male Relatives of Women with Polycystic Ovary Syndrome Is Related to High Rates of Obesity - Coviello, Andrea D. (The Endocrine Society, 2009)
Context: Women with polycystic ovary syndrome (PCOS) have twice the risk for metabolic syndrome (MetS) compared to women from the general population. Mothers and sisters of affected women also have an increased prevalence of MetS. Objective: The aim of the study was to determine the prevalence of MetS in fathers and brothers of women with PCOS compared to men from the general population. Design and Setting: We conducted a cross-sectional observational study at academic medical centers. Participants: A total of 211 fathers and 58 brothers of women with PCOS were studied and compared to 1153 and 582 Third National Health and Nutrition Survey (NHANES III) men of similar age and race/ethnicity, respectively. Main Outcome Measure: We measured MetS prevalence. Results: The prevalence of MetS was increased in fathers (42 vs. 32%; P = 0.006) and brothers (22 vs. 9%; P = 0.001) compared to NHANES III men. Fathers and brothers had higher body mass index (BMI) than NHANES III men (P < 0.0001). MetS rates were similar in fathers and brothers compared to NHANES III groups after adjusting for BMI. Total testosterone was inversely related to MetS in both fathers and brothers, but this relationship was also accounted for by the higher BMI in male relatives. Conclusion: Male relatives of women with PCOS had increased prevalence rates of MetS and obesity compared to the general U.S. male population from NHANES III. In contrast to women with PCOS and their female relatives, the higher prevalence of MetS in male relatives was accounted for by elevated BMI. These findings suggest that the high rates of MetS in male relatives of women with PCOS are related to higher rates of obesity than the general population.